Metal Oxide Nanoparticles in Therapeutic Regulation of Macrophage Functions - Marina S. Dukhinova (Nanomaterials, 2019)
Macrophages are components of the innate immune system that control a plethora of biological processes. Macrophages can be activated towards pro-inflammatory (M1) or anti-inflammatory (M2) phenotypes depending on the cue; however, polarization may be altered in bacterial and viral infections, cancer, or autoimmune diseases. Metal (zinc, iron, titanium, copper, etc.) oxide nanoparticles are widely used in therapeutic applications as drugs, nanocarriers, and diagnostic tools. Macrophages can recognize and engulf nanoparticles, while the influence of macrophage-nanoparticle interaction on cell polarization remains unclear. In this review, we summarize the molecular mechanisms that drive macrophage activation phenotypes and functions upon interaction with nanoparticles in an inflammatory microenvironment. The manifold effects of metal oxide nanoparticles on macrophages depend on the type of metal and the route of synthesis. While largely considered as drug transporters, metal oxide nanoparticles nevertheless have an immunotherapeutic potential, as they can evoke pro- or anti-inflammatory effects on macrophages and become essential for macrophage profiling in cancer, wound healing, infections, and autoimmunity.